An Examination of Records Management in Private Sector Agencies in Kabale Municipality: A Case Study of Kigezi Private Sector. - Kakuru, Danis (Kabale University, 2024)
This study examined the role of records management in the promotion of human rights in an organization in a case study of the Kigezi private sector in Kabale municipality. The objectives of the study were: to identify the role of records management, to examine the challenges faced in records management, and to suggest possible solutions to challenges faced in records management in the Kigezi private sector in Kabale municipality. A descriptive research design was used. Self-administered questionnaires and interview guides were used in collecting data from 40 respondents using purposive and simple random sampling techniques. The data was analyzed using Excel, a computer software to generate descriptive statistics such as frequencies and percentages and they were presented in tables and text. In the study findings on the role of records management in the Kigezi private sector in Kabale municipality, the highest number of the respondents mentioned improved decision-making while the least number of the respondents mentioned financial value. Other respondents mentioned legal value, administrative value and information resource for strategic planning purposes, on challenges of records management in Kigezi private sector in Kabale municipality the highest number of respondents mentioned lack the basic skills and competences for handling records and archives, the lowest number of respondents mentioned weak legislative and organizational infrastructures, others mentioned phobia for computers, absence of an archival institution and inadequate finance and on possible solutions to challenges of records management in Kigezi private sector in Kabale municipality the highest number of respondents mentioned provision of quality leadership, the lowest number of respondents talked that there should be reference of Records, others mentioned that there should be enough storage of records, there should be facilities for staff, provision of quality services to customers based on their needs and provision of high quality information on federal government operations. On recommendations, there should be facilities for Staff. Staff needs suitable working and recreational accommodation, following the standards in effect within the government or organization, there should be the provision of quality leadership to promote the efficient management of organizations' resources correctly, and there should be the provision of quality services to customers based on their needs that is changing the view of management from sole control to service, Enhance customer focus through strong partnerships; Commit to achieving high standards of customer services, there should be a need to provide high-quality information on federal government operations which fully supports financial and performance reporting, establish standards and definitions and all top management should be committed to implementing effective and efficient internal controls. Internal controls are processes, both administrative and program-specific that ensure programs achieve their intended results, and that organizations realize their goals.